Accurate Analysis of Practical 3D Periodic Leaky-Wave Patch Antennas - Mohammad R. Zunoubi; Hassan A. Kalhor (International Journal of Antennas and Propagation)
This paper presents a new analysis method based on the finite integral technique (FIT) of practical three-dimensional leaky-wave antennas comprised of a finite number of patches arranged in arrays. Radiation patterns and scattering parameters are calculated and compared with corresponding measured results to demonstrate the adequacy and the accuracy of the proposed method. The technique is then used as an antenna design tool to obtain the desired radiation patterns and beam scanning by selective choice of array elements dimensions, spacing, and substrate parameters.